Valor alimentar de dietas com azevém (Lolium multiflorum, Lam.) e suplementação nitrogenada ou energética - Amaral, Glaucia Azevedo do (2008)
The present study was carried out to determine the effects of supplementing fresh ryegrass forage based diets with starch, rumen degradable or undegradable protein sources on intake, digestion and nitrogen retention, rumen digestibility and the duodenal nitrogen flow. Ten Corriedale lambs (26 kg mean body weight), kept in metabolic cages were used in a 5 x 5 Latin Square experimental design. Five lambs were previously fitted with permanent ruminal and duodenal cannulae. Treatments tested were: fresh ryegrass forage cut daily and feed without supplementation (AZ); or same forage supplemented with either cassava meal (FM); calcium caseinate (CA), corn gluten meal 21% CP (FMG 21) or corn gluten meal 60% CP (FGM 60). Feeding FGM 21, FGM 60 and CA increased (P<0.05) intake of total dry matter (DM) (P<0.05), organic matter (OM) and digestible organic matter. True digestibility of OM and neutral detergent fibre (NDF) digestibility were similar between treatments, whereas CA and FM treatments increased DM and OM digestibilities. Nitrogen intake was higher (P<0.05) in lambs receiving nitrogen supplements, but microbial N synthesis and N retention was similar between treatments. Ruminal pH values and ammonia N concentration varied in a cubic (P<0.05) way wit time after feeding. Duodenal flux of amino acids was higher (P<0.05) for lambs consuming the FGM 60 supplement. All supplements increased (P<0.05) apparent and true OM ruminal digestibility. The efficiency of rumen microbial N synthesis decreased (P<0.05) in animals fed FGM 21, CA or FM supplements. In conclusion all supplements increased intake of MOD, but only supplement containing rumen undegradable protein increased the amino acids to lambs fed with ryegrass.